ACTION RESEARCH FOR THE 21ST CENTURY: EXPLORING NEW EDUCATIONAL PATHWAYS - Wood, Lesley (South African Journal of Higher Education, 2016)
Twenty years into democracy in South Africa, poverty and disease continue to limit the life prospects of the majority of people. As researchers in higher education, we have an opportunity, not to mention moral obligation, to direct our research towards finding ways to ensure that the expected fruits of democracy can be more evenly dispersed throughout society. Yet, in general, the knowledge produced by the academy has had little positive impact on the quality of life of those we conduct our research on. This article argues for the need to adopt more inclusive and participatory paradigms and methodologies that challenge entrenched views that research is the prerogative of the academy. In particular, I propose that an action research paradigm may offer suitable ways to navigate new educational pathways suited for improving and sustaining social life in the 21st century. Such an approach will help to ensure that academic research remains relevant in today’s complex and fast-changing world. KEYWORDS: academic research; community development; educational research; higher education; indigenous knowledge; participatory action research.